ROLE OF OPERATION RESEARCH METHODS IN TRENDS OF LOGISTICS AND TRANSPORTATION - khan, Khawar Ahmed; Awais, Muhammad; khan, Naveed Ahmed; khan, Salman; Ali, Maryam (The journal of contemporary issues in business and government, 2021)
OR has been instrumental in making transportation processes more efficient, and companies compete to tackle complex logistics and transport problems in a way that has been competitive since its beginning. To improve decision-making,OR as a discipline of systemic nature has tackled the complexity of issues and interconnections among systems components. This study intends to view how OR methods are used in the latest transportation and logistics trends. Different Era's of the growth of OR's contributions to transportation and logistics with the development of information and communication technology (ICT) has been presented. This study filled a gap in the existing literature by describing the latest prevailing trends using OR methods in the context of transportation and logistics and the previous study. Results indicate that operational research is more important now than ever before, and can support new technologies and trends.